2016
DOI: 10.1111/1346-8138.13309
|View full text |Cite
|
Sign up to set email alerts
|

Toxic epidermal necrolysis with isolated neutropenia related to the use of levetiracetam

Abstract: Toxic epidermal necrolysis with isolated neutropenia related to the use of levetiracetam Dear Editor, Levetiracetam (LEV) is a second-generation anticonvulsant that belongs to the category of non-aromatic antiepileptic drugs (AED) and does not form an arene oxide. It has been considered relatively safe compared with other aromatic AED. Toxic epidermal necrolysis (TEN) induced by LEV is extremely rare and, to date, only four cases of TEN or Stevens-Johnson syndrome with LEV have been reported worldwide. 1,2 Fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…106 Patients with SJS/TEN may develop neutropenia, especially in severe cases. 116,117 The role of recombinant human G-CSF in this setting is uncertain (median 5, DI 0.32). 118,119…”
Section: Infection Surveillancementioning
confidence: 99%
“…106 Patients with SJS/TEN may develop neutropenia, especially in severe cases. 116,117 The role of recombinant human G-CSF in this setting is uncertain (median 5, DI 0.32). 118,119…”
Section: Infection Surveillancementioning
confidence: 99%
“…Whether LEV causes hematological changes is controversial. Neutropenia, decreased lymphocyte count, or thrombocytopenia induced by LEV has been reported [26][27][28][29][30], while Dinopoulos et al [26] reported decreased lymphocyte count with no decrease in total WBC count. In our study, there were no significant differences between pre-and post-treatment values in all the he-matological parameters examined in patients administered LEV.…”
Section: Discussionmentioning
confidence: 98%